Analisa Drug Related Problems pada Pasien Dislipidemia di Bangsal Rawat Inap dan Rawat Jalan Penyakit dalam RSUP Dr. M. Djamil Padang - Arsil, Yuliana; Arifin, Helmi; Darwin, Deswinar; Raveinal, Raveinal (Jurnal Sains dan Teknologi Farmasi, 2011)
Dyslipidemia is an abnormality of lipid metabolism, which is characterized by elevated or reduced plasma lipid fractions. Dyslipidemia is a major risk factor of cardiovascular disease. An Improve of lipid profile may reduce the risk of cardiovascular disease. This research was conducted to determine the Drug Related Problems (DRPs) occured in patients with dyslipidemia. This research was a prospective observational study using descriptive cross sectional approach, performed on dyslipidemia patients with or without comorbidities in outpatient and inpatient of Internal Medicine DR. M. Djamil Padang from March to May 2011. Evaluation of the data was carried outdescriptively. Results showed that type of DRPs occurred from 11 dyslipidemia patients with or without comorbidities on inpatient of Internal Medicine were drug interactions in 4 patients, adverse drug reactions in 2 patients, noncompliance in 2 patients, dosage too high in 1 patient, inappropriate drug administration interval in 1 patient while other components of DRPs had no problem. In the outpatient of Internal Medicine, DRPs occured at 98 patients of dyslipidemia with or without accompanying diseases were drug interactions in 26 patients, patient noncompliance in 22 patients, adverse drug reactions in 13 patients, dosage too low in 5 patients, drug therapy without medical indications in 4 patients, inappropriate drug administration interval in 3 patients while other components DRPs had no problem. Drug interactions consisted of pharmacokinetic and pharmacodynamic interactions. In practice, those can be accommodates by separating their administration and monitoring of drug interaction. Meanwhile, toxic drug interactions were not found.